Influence of Microstructure on the Properties of a Cold Drawn Alpha-Beth Cu-Zn-Al Alloy - Dewa Nyoman Adnyana (Institute for Research and Community Services (LPPM) ITB, 1983)
Abstract. In order to improve its drawability at room temperature, the large strain deformation behavior of a Cu-Zn-Al alloy with a two-phase Î± + Î² structure has been studied. Mechanical tests and quantitative metallography on wire specimens in different stages of the drawing process allowed to come to a better understanding of structure-property relationship. The relative deformation of the two phases has been found to depend on various factors such as the hardness difference between the two phases the drawing strain and the shape indices of the constituents. Sari. Sebuah panduan Cu-Zn-Al dengan struktur a+B, diuji tarik melalui proses